Exposure to Aroclor 1254 persistently suppresses the functions of pancreatic β-cells and deteriorates glucose homeostasis in male mice. (June 2019) - Xi, Zhihui; Fang, Lu; Xu, Jing; Li, Bingshui; Zuo, Zhenghong; Lv, Liangju; Wang, Chonggang
Abstract: Polychlorinated biphenyls (PCBs) are a class of persistent organic pollutants that have been shown to be related to the occurrence of type 2 diabetes mellitus (T2DM). Nevertheless, it is necessary to further explore the development of T2DM caused by PCBs and its underlying mechanisms. In the present study, 21-day-old C57BL/6 male mice were orally treated with Aroclor 1254 (0.5, 5, 50 or 500 μg kg −1 ) once every three days. After exposure for 66 d, the mice showed impaired glucose tolerance, 13% and 14% increased fasting serum insulin levels (FSIL), and 63% and 69% increases of the pancreatic β-cell mass in the 50 and 500 μg kg −1 groups, respectively. After stopping exposure for 90 d, treated mice returned to normoglycemia and normal FSIL. After re-exposure of these recovered mice to Aroclor 1254 for 30 d, fasting plasma glucose showed 15%, 28% and 16% increase in the 5, 50 and 500 μg kg −1 treatments, FSIL exhibited 35%, 27%, 30% and 32% decrease in the 0.5, 5, 50 or 500 μg kg −1 groups respectively, and there was no change in pancreatic β-cell mass. Transcription of the pancreatic insulin gene ( Ins2 ) was significantly down-regulated in the 50 and 500 μg kg −1 groups, while DNA-methylation levels were simultaneously increased in the Ins2 promoter during the course of exposure, recovery and re-exposure. Reduced insulin levels were initially rescued by a compensative increase in β-cell mass. However, β-cell mass eventually failed to make sufficient levels of insulin, resulting in significant increases in fasting blood glucose, and indicating the development of T2DM. Graphical abstract: Image 1 Highlights: Aroclor 1254 disturbed glucose homeostasis and serum insulin levels in male mice. Insulin resistance and insulin levels were recovered after stopping exposure. Re-exposure caused elevated fasting blood glucose and reduced insulin levels. The transcription of pancreatic Ins2 was down-regulated during the course. DNA-methylation level was increased in the Ins2 promotor during the course. Abstract : The mRNA levels of pancreatic Ins2 were invariably down-regulated in mice during exposure, recovery and re-exposure to Aroclor 1254.